ANALISIS PENGARUH DETERMINANT LOYALITAS PELANGGAN HANDPHONE NOKIA SERTA DAMPAKNYA PADA WORD O MOUTH (Studi Pada - PRATOMO, BIMO (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2011)
This study focuses on factors that affect customer loyalty and its impact on word of mouth. Therapid development of technology and information and the change in mindset and behavior ofpeople force the company to be able to provide excellent service and qualified products so as tosatisfy its customers better, which in turn can foster customer loyalty, thus encouraging positiveword of mouth. Empirical data found indicate a problem on Nokia mobile phone customer loyalty.Based on these, the problem formulated in this study is â€œHow to increase customer loyaltyimpacting on word of mouth?â€To answer the research problem, we conducted some literature reviews and previous researchjournals which in turn direct the researcher to develop four hypotheses of five examinedconstructs. The hypotheses were tested by using statistical software AMOS 16. Empirical dataneeded to test the hypotheses were obtained from 150 questionnaires distributed to respondentswho are the Regular 1 and Regular 2 students of the Faculty of Economics of Undip Semarang.According to the analysis of the research model shows that the model can be accepted basedon the feasibility of the model. Thus, the causality test results of the hypotheses show that thereis a positive and significant influence of the perception of quality, buying experience, and productsexcellence on customer loyalty and there is a positive and significant influence of customerloyalty on word of mouth.